FATF Recommendations in Adopting Risk-Based Approach (RBA) in Anti-Money Laundering Supervisory-Control Structure and Iran's Legislative Position - Amir Jamali Hajiani; Esmaeil Abdollahi; Ahmad Mirzaei (پژوهشهای حقوقی)
"Supervision and Control", as an essential part of any Anti-Money Laundering Management System, is of great importance in preventing and combating the purification of criminal proceeds. Since the Financial Action Task Force, recommended countries and those subject to anti-money laundering laws to adopt a "Risk-Based Approach" and considered it as a fundamental principle in combat money laundering, by adopting such an approach in the national and intra-organizational supervisory and control structure, it is possible to identify the highest risks and to direct resources according to priorities. Considering the importance of the matter, in this research, by studying the documents and recommendations issued by FATF and Iran's Anti-Money Laundering Law (amended 2018), in a descriptive-analytical method, while identifying and explaining the standards of adopting a risk-based approach in anti-money laundering supervisory and control structure with a view to draw a road map, the legislative position of Iran will be analyzed in this regard. In conclusion, by identifying the components of adopting a standard risk-based approach and studying Iran's legislative approach, the results show that in Iran's anti-money laundering supervisory and control structure, with the formation of the necessary institutions, the adoption of a risk-based approach has been considered at both national and intra-organizational levels, and its manifestation can be seen in the prediction of "National Risk Assessment Workgroup", "National Risk Assessment Document" and "Action Plan".